They raised me up : a black single mother and the women who inspired her - Wilkins, Carolyn (Carolyn Marie) (University of Missouri Press, 2013)
At the height of the cocaine-fueled 1980s, the author left a disastrous marriage in Washington State and, hoping to make it in the music business, moved with her four-year-old daughter to a gritty working-class town on the edge of Boston. This is the story of her battle to succeed in the world of jam sessions and jazz clubs - a man's world where women were seen as either sex objects or doormats. To survive, she had to find a way to pay the bills, overcome a crippling case of stage fright, fend off a series of unsuitable men, and most important, find a reliable babysitter. Alternating with Carolyn's story are the stories of her ancestors and mentors - five musically gifted women who struggled to realize their dreams at the turn of the twentieth century: Philippa Schuyler; Marjory Jackson; Lilly Pruett; Ruth Lipscomb; and Alberta Sweeney. -- Publisher's description.